Tracer study to assess the employability of graduates and quality of a nursing program: A descriptive cross-sectional survey - Dzomeku, Veronica M. (Elsevier, 2025)
Background
Contribution of nursing is crucial for Universal Health Coverage and achieving Sustainable Development Goal 3. Tracer studies help evaluate accountability and demonstrate the impact of nursing educational institutions in a highly competitive job market. The study aimed at assessing the employability of nursing graduates, and perceived quality of the nursing program they pursued in a public tertiary institution in Ghana.
Method
The study employed a descriptive cross-sectional survey. One hundred and ten (110) nursing graduates responded to a web-based survey. The data were gathered using a customized questionnaire based on the Tarlac State University Graduates Tracer Questionnaire. Data were collected via google forms, and analyzed using descriptive and inferential statistics.
Results
Majority of the participants were females (n = 64, 58.2 %). Most of the participants had completed a Bachelor’s degree at the tertiary institution (n = 101, 91.8 %). A significant proportion of the participants were gainfully employed during the study period (n = 102, 92.7 %) with majority of them working in the public sector (n = 81, 79.4 %). The quality of the diploma or degree program obtained was rated good in most of the areas by over 50 % of the participants. There was no statistically significant association between the highest educational qualification of participants and their perceptions on the quality of the nursing program.
Conclusion
There is the need to conduct this kind of tracer study on a regular basis to keep track of graduate’s progress and obtain feedback on the quality of programs being offered so as to meet the ever-changing needs of society.